2021
DOI: 10.1111/jipb.13049
|View full text |Cite
|
Sign up to set email alerts
|

Rice FLOURY ENDOSPERM 18 encodes a pentatricopeptide repeat protein required for 5′ processing of mitochondrial nad5 messenger RNA and endosperm development

Abstract: Pentatricopeptide repeat (PPR) proteins, composing one of the largest protein families in plants, are involved in RNA binding and regulation of organelle RNA metabolism at the posttranscriptional level. Although several PPR proteins have been implicated in endosperm development in rice (Oryza sativa), the molecular functions of many PPRs remain obscure. Here, we identified a rice endosperm mutant named floury endosperm 18 (flo18) with pleiotropic defects in both reproductive and vegetative development. Map-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…Rice endosperm is known to be an excellent system for elucidating how gene networks regulate starch synthesis and amyloplast development (Nelson and Pan 2003;Satoh and Omura 1981), so various mutants with defective endosperm have been screened for further research. In terms of appearance, oury endosperm mutants can generally be divided into two types: completely oury endosperm mutant (such as FLO13 (Hu et al 2018), FLO14 (Xue et al 2019), FLO16 (Teng et al 2019) and FLO18 (Yu et al 2020)) and partially oury endosperm mutant (such as FLO4 (Kang et al 2005), FLO7 and FLO15 (You et al 2019)). Interestingly, similar to previously reported o7 mutant, the peripheral region of o19 mutant grain also appeared oury-white (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rice endosperm is known to be an excellent system for elucidating how gene networks regulate starch synthesis and amyloplast development (Nelson and Pan 2003;Satoh and Omura 1981), so various mutants with defective endosperm have been screened for further research. In terms of appearance, oury endosperm mutants can generally be divided into two types: completely oury endosperm mutant (such as FLO13 (Hu et al 2018), FLO14 (Xue et al 2019), FLO16 (Teng et al 2019) and FLO18 (Yu et al 2020)) and partially oury endosperm mutant (such as FLO4 (Kang et al 2005), FLO7 and FLO15 (You et al 2019)). Interestingly, similar to previously reported o7 mutant, the peripheral region of o19 mutant grain also appeared oury-white (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…So far, many genes responsible for oury phenotype have been identi ed. Some genes are directly involved in starch synthesis and storage protein transport (including OsAPL2 (Wei et al 2016), FLO5 (Ryoo et al 2007), OsBEIIb (Tanaka et al 2004), OsRab5a (Wang et al 2010), OsVPS9a (Liu et al 2013), GPA3 (Ren et al 2014), GOT1B (Wang et al 2016), GPA5 (Ren et al 2020)). Several transcription factors regulate the expression of starch or protein synthesis-related genes (including RISBZ1/OsbZIP58 (Wang et al 2013), RPBF (Kawakatsu et al 2009), bHLH144 (Bello et al 2018), RSR1 (Fu and Xue 2010)), and there are more genes that indirectly affect starch and protein (including PPR5 (Zhang et al 2020c), FLO8 (Long et al 2017), FLO16 (Teng et al 2019), FLO14 (Xue et al 2019), FLO15 (You et al 2019), FLO18 (Yu et al 2020), etc.…”
Section: Introductionmentioning
confidence: 99%
“…GFP signals were observed in the nucleus and cytoplasm, indicating that EDR1 was localized to the nucleus and cytoplasm (Figure 5B). EDR1 influences grain quality Defects in endosperm development always cause grain quality changes (Wang et al, 2008;Zhang et al, 2016;Wu et al, 2019;Yu et al, 2021). The above results indicated that EDR1 influences endosperm development in rice, so grain quality was analyzed.…”
Section: Expression Pattern and Subcellular Localization Of Edr1mentioning
confidence: 92%
“…After cellularization of the endosperm, as well as differentiation and maturation, the inner starchy endosperm and an outer aleurone layer are subsequently formed (Krishnan and Dayanandan, 2003; Wu et al, 2016). Moreover, sugars from maternal tissues are transported to the endosperm for starch biosynthesis and accumulation, and a series of enzymatic reactions are involved in these processes (Weschke et al, 2000; Patrick and Offler, 2001; James et al, 2003; Yu et al, 2021). Many genes encoding starch biosynthesis enzymes in rice influence endosperm development, and mutations in these genes can lead to abnormal endosperm development (James et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…FLO10, FLO14, and FLO18 encode pentatricopeptide repeat (PPR) proteins involved in RNA binding and metabolism in plant mitochondria. The processing of mitochondrial NAD genes, such as NAD1 and NAD5, was defective in flo10, flo14, or flo18 mutants (Wu et al, 2019;Xue et al, 2019;Yu et al, 2020a). NAD genes encode subunits of NADH dehydrogenase that are essential for ATP production and mitochondrial development.…”
Section: Flo Genes Play Important Roles In Endosperm Development Of Ricementioning
confidence: 99%